Enabling retail food supply chain, viability and resilience in pandemic disruptions by digitalization – a conceptual perspective - Ahmed Zainul Abideen Muzamil; Jaafar Pyeman; Sofianita binti Mutalib; Kamalia Azma binti Kamaruddin; Norsariah binti Abdul Rahman (International Journal of Industrial Engineering and Operations Management)
Purpose – Supply chain disruptions are a significant risk to businesses in a global marketplace because they make it more challenging for suppliers to effectively transport goods and services to customers. Therefore, it is essential to comprehend how these disruptions affect the retail food supply chain during pandemics and explore how digitalization might help to mitigate these issues in the future. Design/methodology/approach – A hybrid systematic review and analysis was conducted by retrieving data set from the scopus database using strong keyword search strategy. Later a content analysis was also done to gain more insights on the proposed research. Findings – The results show that there are several possibilities enabling optimal scenario planning supply chain disruptions and mitigation. In this area, digitalization improves customer satisfaction and logistical efficiency, particularly in transportation and network optimization. In order to cope with uncertainty and grasp significant enhancements proactive strategies and collaboration that are guided by scenario planning and digitalization assist in developing robust supply chains that are sufficiently adaptable to adapt to shifting market conditions. Research limitations/implications – The study is limited to research papers indexed in Scopus from 2015 to 2023 with a more comprehensive review of retail food supply chain disruptions. Practical implications – This research provides practical insights for retail food supply chain managers, highlighting the importance of digital maturity and scenario planning by leveraging digital tools and proactive strategies to improve logistical efficiency. Social implications – This study helps in building resilient supply chains ensures the reliable availability, and food security of essential goods, particularly during crises. Originality/value – This research uniquely links digitalization and scenario planning to managing supply chain disruptions, highlighting how digital tools and strategic planning enhance resilience and adaptability in the retail food supply chain.